Reproducibility of Intra-Abdominal Pressure Measured During Physical Activities Via a Wireless Vaginal Transducer. Issue 3 (May 2015) - Egger, Marlene J.; Hamad, Nadia M.; Hitchcock, Robert W.; Coleman, Tanner J.; Shaw, Janet M.; Hsu, Yvonne; Nygaard, Ingrid E.
Abstract : Aims: In the urodynamics laboratory setting, a wireless pressure transducer, developed to facilitate research exploring intra-abdominal pressure (IAP) and pelvic floor disorders, was highly accurate. We aimed to study reproducibility of IAP measured using this transducer in women during activities performed in an exercise science laboratory. Methods: Fifty-seven women (mean ± SD, age 30.4 ±9.3 years; body mass index, 22.4 ± 2.68 kg/m 2 ) completed 2 standardized activity sessions using the same transducer at least 3 days apart. Pressure data for 31 activities were transmitted wirelessly to a base station and analyzed for mean net maximal IAP, area under the curve, and first moment of the area. Activities included typical exercises, lifting 13.6 to 18.2 kg, and simulated household tasks. Analysis for test-retest reliability included Bland-Altman plots with absolute limits of agreement, Wilcoxon signed rank tests to assess significant differences between sessions, intraclass correlations, and κ statistics to assess intersession agreement in highest versus other quintiles of maximal IAP. Results: Few activities exhibited significant differences between sessions in maximal IAP, or in area under the curve and first moment of the area values. For 13 activities, the agreement between repeat measures of maximal IAP was better than ±10 cm H2 0; for 20 activities, better than ±15 cm H2 0. The absolute limits of agreement increased with mean IAP. The highest quintile of IAP demonstrated fair/substantial agreement between sessions in 25 of 30 activities. Conclusions: Reproducibility of IAP depends on the activity undertaken. Interventions geared toward lowering IAP should account for this, maximize efforts to improve IAP reproducibility. Abstract : The reproducibility of intra-abdominal pressure measured using a vaginal transducer depends on the activity undertaken and increases as mean intra-abdominal pressure increases.